Boosting Preservice Teachers' Competence and Online Teaching Readiness through E-Practicum during the COVID-19 Outbreak - Pinar Ersin; Derin Atay; Enisa Mede (Cranmore Publishing, 2020)
The Coronavirus (COVID-19) outbreak has caused disruptions in education in Turkey, as it has in many parts of the world. Faculties of Education that require practice teaching (practicum) are affected as well; due to the shutdown, pre-service English language teachers (PTs) are deprived of the field experience and actual classroom teaching practices in authentic school settings. Practicum constitutes an important part of teacher education and during practicum, "cooperating" teachers (i.e. teachers at practicum schools) and university instructors as teaching practice supervisors play crucial roles in equipping PTs with necessary theoretical and practical skills. The present study took place in the English Language Education program of a competitive state university in Turkey. At the university, all theory-oriented courses moved to synchronous platforms without much difficulty with almost full attendance of the students. As for the practicum, Turkish Higher Education Council let the universities decide for themselves. As researchers working at two different universities, Bahçeşehir University and Marmara University, Istanbul, Turkey, we designed an alternative practice to meet the needs of PTs and maintain the quality of the practicum: "e-practicum" under the supervision of the university supervisor who acted as the "e-mentor". The aim was to increase PTs' teaching competence and prepare them for online teaching. A virtual classroom consisting of twenty-five PTs was formed and six PTs performed microteaching to their peers who acted as students by using Zoom. After the e-practicum sessions, peers gave detailed feedback to the teacher PTs. The university supervisor provided e-mentoring right after each session. Then, each teacher PT reflected on e-practicum experience and e-mentoring. The findings revealed that PTs found the e-practicum useful because it helped them overcome online teaching fears.